Academic Reading Challenges and Coping Strategies: A Mixed-Methods Study of Indonesian EFL Undergraduate Students - Kelderak, Samawati (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2023)
This study investigates academic reading difficulties and coping strategies among undergraduate English as Foreign Language (EFL) students in the English Education Study Program at Pattimura University, Indonesia. Using a mixed-methods case study design, data were collected from 40 undergraduate students through questionnaires and group interviews. Quantitative analysis revealed three primary challenges: understanding specialist vocabulary (M=3.8), taking brief and relevant notes (M=3.8), and working out meanings of difficult words (M=4.0). Qualitative findings identified four main coping strategies: technology utilization, systematic note-taking, text rereading, and mind mapping techniques. The results indicate that while students face significant vocabulary-related challenges in academic reading, they have developed sophisticated strategies to overcome these difficulties. This study contributes to understanding EFL students' academic reading experiences in Indonesian higher education contexts and provides insights for developing targeted pedagogical interventions.